Masyarakat Sipil Dan Prospeknya Di Indonesia - Ida Farida (PUBLICA, 2011)
Civil society is a space that lies between the countries on one hand and society on the other hand. There is an association of people who are voluntary and a network of relationships between the associations in that space. The realization of sustainable human development is not only dependent on the country that can govern well and the private sector that can provide job and income, but also depends on civil society organization that facilitate social and political interaction and mobilize the various groups in society to engage in social activity, economy and politic. Indonesian society is a highly pluralistic society or particularly called as the society that has a very high level of social fragmentation whether it sourced on economic issues, social culture, ethnicity and also the political field. Those are the things that inhibit the growth and development of civil society or at least slow down its development.